Kurikulum Merdeka Belajar dan Implementasinya dalam Pendidikan Kristen pada Tingkat Sekolah Dasar di Pelosok Kepulauan Nias - Duha, Asni Darmayanti (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2024)
The independent learning curriculum is one of the programs for developing and improving the quality of education in Indonesia. However, the problems that occur with the implementation of the free learning curriculum in remote areas of the Nias Islands, especially in elementary schools, are the lack of preparedness of human resources, both educators who are not well equipped and students who are not ready to accept the free learning curriculum system and inadequate infrastructure. adequate to support the successful implementation of the independent learning curriculum in Christian education. The aims of this research consist of first, revealing the problems that occur so that they become evaluation material for both the central, provincial, and regional governments as well as for private educational institutions. Second, to offer a simple solution as an effort to implement the independent learning curriculum in remote areas of the Nias Islands, namely providing extra (gradual and continuous) teacher training and completing infrastructure. The research method used is a literature study. Based on the results of data analysis, it can be concluded that efforts to implement the independent learning curriculum in Christian education at the elementary school level in remote areas of the Nias Islands have not gone well and maximally, thereby affecting the quality of human resources produced. AbstrakKurikulum merdeka belajar merupakan salah satu program pengembangan dan peningkatkan mutu pendidikan di Indonesia. Namun, persoalan yang terjadi pada penerapan kurikulum merdeka belajar tersebut pada pelosok Kepulauan Nias, khususnya pada satu pendidikan Sekolah Dasar, yakni kurangnya kesiapan sumber daya manusia baik pendidik yang tidak dibekali dengan baik maupun siswa yang tidak siap menerima sistem kurikulum merdeka belajar dan sarana prasarana yang kurang memadai sebagai penunjang keberhasilan penerapan kurikulum merdeka belajar dalam pendidikan Kristen. Tujuan penelitian ini terdiri atas: pertama, untuk mengungkapkan masalah yang terjadi sehingga menjadi bahan evaluasi baik bagi pemerintah pusat, provinsi dan daerah serta bagi lembaga pendidikan swasta. Kedua, untuk menawarkan solusi yang sederhana sebagai upaya dalam menerapkan kurikulum merdeka belajar di pelosok Kepulauan Nias, yakni melakukan pembekalan para guru secara ekstra (bertahap dan berkesinambungan) dan melengkapi sarana prasana. Metode penelitian yang digunakan adalah studi pustaka. Berdasarkan hasil analisis data, maka dapat disimpulkan bahwa upaya penerapan kurikulum merdeka belajar dalam pendidikan Kristen pada tingkat sekolah dasar di pelosok Kepulauan Nias belum berjalan dengan baik dan maksimal sehingga memengaruhi kualitas sumber daya manusia yang dihasilkan.